Mixed method study: Self-injury behavior based on intensity of social media (Tiktok) use in students - Jesica, Feni; Ningsih, Ruly (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
High use of social media (TikTok) encourages students to commit self-injury. This study aims to examine the differences in self-injury behavior seen from the intensity of social media use (TikTok) in students at Seyegan 1 State Junior High School. The approach used in this study is a mixed method. The validity of the quantitative instrument focuses on the confirmatory factor analysis (CFA) statistical test. Reliability is measured using Cronbach's Alpha. Qualitative data credibility testing is carried out by analyzing negative cases. Qualitative data analysis is carried out using an interactive model. The results of quantitative data analysis show significant differences between self-injury behavior seen from the intensity of social media use (TikTok). The higher the intensity of social media use (TikTok), the greater the probability of self-injury. The results of qualitative data analysis show differences in the intensity of social media use (TikTok) in the low, medium, high, and very high categories of self-injury which is characterized by forms of behavior such as hitting walls, biting skin, cutting, scratching arms and slapping themselves. The cause of self-injury behavior in students is because there is no other way to channel emotions. The subject learned this behavior by imitating others from TikTok content. The subject hurts themselves using sharp objects. The place chosen to hurt themselves is usually at home, in a room, or in a quiet place. The main reasons for committing self-injury are feeling that they have mental health problems, stress, depression, and lack of understanding from others. The body parts that are often targeted by self-injury are the arms, hands, and feet. To stop self-injury, the subject needs attention, psychological counseling, family support, and friends. The impact of self-injury provides a temporary sense of calm but worsens emotional conditions and causes physical wounds that are at risk of infection. Excessive use of social media exposes students to negative content that has an impact on increasing anxiety and social relationships.